THE INFLUENCE OF USER SATISFACTION ON REINTENTION TO USE MEDIATED BY E-TRUST IN SHOPEE ECOMMERCE AMONG MANAGEMENT STUDENTS AT MAKASSAR STATE UNIVERSITY - Musdena Musaat; M. Ilham Wardhana Haeruddin; Ilma Wulansari Hasdiansa; Siti Hasbiah; Rahmat Riwayat Abadi (CV. Adiba Aisha Amira, 2025)
This study examines the relationship between user satisfaction, e-trust, and the intention to reuse Shopee eCommerce among management students at Makassar State University. With the proliferation of online shopping platforms, understanding factors influencing users' intention to continue using specific platforms is crucial for both academic research and practical applications. The theoretical framework is grounded in the Technology Acceptance Model (TAM) and the Trust-Commitment Theory, which posit that user satisfaction and e- trust significantly influence users' behavioral intentions in electronic commerce contexts. Data were collected through a structured questionnaire distributed to a sample of management students who have experience using Shopee eCommerce. Results from the analysis indicate a positive relationship between user satisfaction and the intention to reuse Shopee. Furthermore, e-trust mediates the relationship between user satisfaction and reuse intention, suggesting that trust in the platform acts as a significant mechanism through which user satisfaction translates into continued usage intentions. These findings contribute to both theoretical and practical implications for eCommerce platforms, suggesting strategies to enhance user satisfaction and build trust among users to foster loyalty and repeat usage. Limitations and avenues for future research are also discussed.